2018
DOI: 10.1080/10715762.2018.1489132
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NRF2/ARE by convallatoxin sensitises A549 cells to 5-FU-mediated apoptosis

Abstract: NF-E2-related factor 2 (NRF2) regulates transcription of phase II cytoprotective enzymes to protect normal cells against oxidative stress. However, a high level of NRF2 offers a growth advantage, chemoresistance, and radioresistance in cancer. In the present study, we have identified convallatoxin as a novel inhibitor of NRF2/ARE. Suppression of NRF2 by convallatoxin was not transcriptionally mediated, but regulated at the level of proteolysis. Convallatoxin activated GSK-3β and suppression of NRF2 by convalla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Furthermore, the depletion of NRF2 was found to inhibit the induction of apoptosis by KEAP1 depletion. Despite more and more studies investigating Nrf2/Keap1 modulated death of multiple cell lines, [32][33][34] Some other mechanisms associated with Nrf2 stimulation have been reported, including acetylation, phosphorylation, and cysteine post-translational modification. These modifications regulate activities of glycogen synthase kinase-3 beta (GSK3b), phosphatidylinositol 3-kinase pathway (PI3K/AKT), PKC, MAPK, as well as extracellular regulated protein kinases (ERKs).…”
Section: R E T R a Cmentioning
confidence: 99%
“…Furthermore, the depletion of NRF2 was found to inhibit the induction of apoptosis by KEAP1 depletion. Despite more and more studies investigating Nrf2/Keap1 modulated death of multiple cell lines, [32][33][34] Some other mechanisms associated with Nrf2 stimulation have been reported, including acetylation, phosphorylation, and cysteine post-translational modification. These modifications regulate activities of glycogen synthase kinase-3 beta (GSK3b), phosphatidylinositol 3-kinase pathway (PI3K/AKT), PKC, MAPK, as well as extracellular regulated protein kinases (ERKs).…”
Section: R E T R a Cmentioning
confidence: 99%
“…Trypan blue exclusion assay also indicated that the viability of A549 and H1299 cells was unaffected by triptolide at concentrations up to 40 nM ( Supplementary Figure S1 ). We have previously identified that convallatoxin inhibits NRF2 and sensitizes A549 cells to cisplatin-induced apoptosis ( Lee et al, 2018a ). Using convallatoxin as a prototypical NRF2 inhibitor, we exposed A549 cells to triptolide, and examined the expression of NRF2 and its target proteins, heme oxygenase-1 (HO-1) and NAD [P]H:quinone oxidoreductase-1 (NQO1) by Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, from a screening of 644 natural compounds, Convallatoxin emerged as a novel and potent NRF2 inhibitor, presumably by promoting GSK-3 β / β -TrCP-dependent but KEAP1-independent proteolysis of NRF2. Notably, Convallatoxin sensitized A549 cells to 5FU-induced apoptosis, providing evidence that this natural compound might be a promising chemotherapeutic adjuvant in NSCLC treatment [300] (see Table 1).…”
Section: Therapeutic Strategies For Nrf2 Inhibition In Cancermentioning
confidence: 99%